A comparative study of Islamic housing finance models and issues. (2nd May 2017) - Baber, Hasnan
Abstract : Purpose: This paper aims to provide comprehensive review of Islamic housing finance models. The paper provides detailed mechanism and solution to contemporary issues of these models.. Design/methodology/approach: This paper is conceptual in nature. Based on an extensive study of literature, this paper explains working of two Islamic models al-Bay' Bithaman Ajil (BBA) and the Musharakah Mutanaqisah (MM) with hypothetical examples. Findings: It was revealed in the study that BBA is just convergence of conventional housing finance and does not fall in line with shariah regulations. MM approach is a relative new concept and strictly following shariah guidelines. MM approach is based on welfare for all rather than profit for few. There were some issues spotted with MM model when implemented on the ground, and hence this study came up with solution to such issues. Research limitations/implications: This paper cannot be tested until the models are practically applied. This MM contract is new and will take some time to be accepted by customers, but its reliability promises it.. Originality/value: This study is original and new, as it finds BBA not permissible which no other study has concluded so far. Also issues in these models, and their solutions were studied first time.